2022
DOI: 10.1007/s11071-021-07092-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear characteristics of a multi-degree-of-freedom wind turbine’s gear transmission system involving friction

Abstract: In this study, a 42-degree-of-freedom (42-DOF) translation-torsion coupling dynamics model of the wind turbine's compound gear transmission system considering time-varying meshing friction, time-varying meshing stiffness, meshing damping, meshing error and backlash is proposed. Considering the different meshing between internal and external teeth of planetary gear, the time-varying meshing stiffness is calculated by using the cantilever beam theory. An improved mesh friction model takes account into the mixing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Li et al [14] established an integrated drivetrain coupling analysis model of wind turbine gearbox considering the effect of nontorque loads, and studied the gearbox vibration responses, gear meshing forces and bearing forces. Zhang et al [15] proposed a 42-degree-of-freedom translation-torsion coupling dynamic model of PGTs involving friction and backlash, and found the complex bifurcation and chaotic behaviors. Li et al [16] formulated a nonlinear time-varying dynamic model of a multistage PGTs with time-varying meshing stiffness and piece-wise backlash nonlinearities, and analyzed the influences of excitation frequency and backlash on bifurcation and chaos properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [14] established an integrated drivetrain coupling analysis model of wind turbine gearbox considering the effect of nontorque loads, and studied the gearbox vibration responses, gear meshing forces and bearing forces. Zhang et al [15] proposed a 42-degree-of-freedom translation-torsion coupling dynamic model of PGTs involving friction and backlash, and found the complex bifurcation and chaotic behaviors. Li et al [16] formulated a nonlinear time-varying dynamic model of a multistage PGTs with time-varying meshing stiffness and piece-wise backlash nonlinearities, and analyzed the influences of excitation frequency and backlash on bifurcation and chaos properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 15. Schematic of the evolution mechanism of multi-stability response decreasing in ω under the synergistic effect of parameter-state space (Corresponding to Fig.14).…”
mentioning
confidence: 99%
“…They concluded that gear eccentricity can regulate the amplitude and frequency of the response. Zhang et al [23] identified nonlinear dynamic characteristics of a wind turbine compound gear transmission system by using the fourth-order RK method. Their investigation discussed complex nonlinear behaviors of the system including periodic, quasi-periodic, and chaotic responses.…”
Section: Introductionmentioning
confidence: 99%